STUDI PRODUKSI GARAM DENGAN METODE PLTS UNTUK PERBANDINGAN AIR LAUT DENGAN AIR TAMBAK - Anwar, Dimas Hijjul; Jamaaluddin, Jamaaluddin; Syahrorini, Syamsudduha; Sulistiyowati, Indah (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
This research discusses the utilisation of Solar Power Plant (PLTS) in the salt production process by comparing the effectiveness of using seawater and pond water. The purpose of this study is to compare the process of making salt using pond water and seawater. The designed system includes automatic heating, temperature control, and automatic pumping system operated with energy from PLTS. The test was conducted for 1.5 hours with a measurement interval of 10 minutes. The results show that seawater produces more salt, namely 6 grams, compared to pond water which only produces 4 grams, with the volume of evaporated water ranging from 5-8 mL each. This difference indicates that the salt content in seawater is higher, making it more efficient for salt production. Although the solar PV system used is not yet fully optimised, this research shows the great potential of using renewable energy in the salt production process that is environmentally friendly and independent from conventional energy supplies.